2014
DOI: 10.1186/1471-2164-15-769
|View full text |Cite
|
Sign up to set email alerts
|

A functional genomics catalogue of activated transcription factors during pathogenesis of pneumococcal disease

Abstract: BackgroundStreptococcus pneumoniae (the pneumococcus) is the world’s foremost microbial pathogen, killing more people each year than HIV, TB or malaria. The capacity to penetrate deeper host tissues contributes substantially to the ability of this organism to cause disease. Here we investigated, for the first time, functional genomics modulation of 3 pneumococcal strains (serotype 2 [D39], serotype 4 [WCH43] and serotype 6A [WCH16]) during transition from the nasopharynx to lungs to blood and to brain of mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Mutations in smrC, encoding the LysR-family transcriptional regulator, SmrC, were the second most common type of mutation (Table 1). SmrC is considered to be a critical virulence regulator that is highly active during infections in mice (Lau et al, 2001;Mahdi et al, 2013Mahdi et al, , 2014. Mutations in smrC arose from selection on multiple carbohydrates suggesting SmrC has a global regulatory influence on carbohydrate metabolism.…”
Section: A Selection For Suppressors Identifies Factors That Relieve mentioning
confidence: 99%
“…Mutations in smrC, encoding the LysR-family transcriptional regulator, SmrC, were the second most common type of mutation (Table 1). SmrC is considered to be a critical virulence regulator that is highly active during infections in mice (Lau et al, 2001;Mahdi et al, 2013Mahdi et al, , 2014. Mutations in smrC arose from selection on multiple carbohydrates suggesting SmrC has a global regulatory influence on carbohydrate metabolism.…”
Section: A Selection For Suppressors Identifies Factors That Relieve mentioning
confidence: 99%
“…In an interesting study, it was found that the 5′ UTR controls variant activity of ERG and of Tmprss2:ERG. Specific arrangements of regulatory elements and variants in upstream non‐coding regions of genes dictate diverse patterns of gene expression . Also, co‐expressed genes commonly share similar regulatory elements in their UTRs and promoter regions that bind specific transcription factors .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In fact, most biomarker/signature discovery studies have focused on coding regions and proteins, and the role of non-coding variants, including those seen in 3′ upstream untranslated regions (3′ UTR), 5′ UTR, intronic variants, and intergenic variants are largely neglected. 7 Non-coding variants may influence microRNA-mRNA interaction, epigenomic regulation, and alternative splicing in cancer induction and progression. The functional impact of intergenic variants in different diseases through alteration in chromatin structure of nearby genes has been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the significant CREs may be associated with the differential expression of the two groups of genes in response to light. DOF proteins are plant specific transcription factors involved in seed development as well as signaling and response to light and phytohormone (Mahdi et al, 2014).…”
Section: Case Study 1: Comparative Promoter Analysis Of Atham1 and Atmentioning
confidence: 99%
“…Recently, it has been demonstrated that CREs on the promoter regions of genes in wild wheat are more variable and frequent than the cultivated wheat which contributes in fast response and better understanding of environmental conditions for wild genotype (Babgohari et al, 2014). Due to the unique characteristic of transcription factors in binding to CREs on promoter regions of different genes, a small number of transcription factors are enough to regulate a considerable number of genes and play the central role in functional genomics (Mahdi et al, 2013;Mahdi et al, 2014). Interestingly, a small number of transcription factors and microRNAs, as the two main commanders of system biology, can regulate a genomic region involved in a particular phenomenon (hot spots) (Alisoltani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%